Potential Arrival Pathway for Highly Pathogenic Avian Influenza H5N1 to Oceania - Plaza, Pablo (2024)
NAIn late 2020, the Highly Pathogenic Avian Influenza A(H5N1) (hereafter, H5N1) fired the most severe panzootic ever recorded, causing alarming mortalities in wildlife and domestic animals, with an increasing risk to humans [1–4]. Almost the entire world has been affected by H5N1; the virus has expanded to new regions such as the Americas and Antarctica for the first time in its evolutionary history [3]. However, no cases of H5N1 have been detected in Oceania to date [5, 6] (only one human case infected outside this continent has been reported [7]). Regions not affected by this virus are of epidemiological importance, as they provide insights about potential limiting factors for its spread (e.g., geographic barriers, environmental features, wild species traits and movement). Moreover, in those areas, there is still time to prepare efficient preventive and mitigation actions to reduce the impact of this pathogen, if we can identify potential pathways of virus arrival. Here, leveraging range maps of suitable host bird species, we suggest a potential pathway of H5N1 arrival to the Oceania region that could be important to consider under the current epidemiological behavior of this virus.